Ancient Greek grammar for the study of the New Testament - Siebenthal, Heinrich von 1945-; Peter Lang GmbH (Oxford Bern Berlin Bruxelles New York Wien Peter Lang, 2019)
"The Ancient Greek Grammar for the Study of the New Testament is a tool for theologians and others interested in interpreting the Greek New Testament. It is a reference grammar that systematically covers all areas relevant to well-founded text interpretation including textgrammar. Combining accuracy with accessibility was one of the main objectives in producing the book. The information it provides is based on the best of traditional and more recent research in the study of Ancient Greek and linguistic communication. Differences between classical and non-classical usage are regularly indicated. The mode of presentation is largely shaped by the needs of prospective users, who are typically unacquainted with the details of linguistic research. Aiming at both a professional quality of content and user-friendly presentation, a tool was produced that aims to be of service to novices and more experienced exegetes alike"--
Previously published as Griechische Grammatik zum Neuen Testament
Includes bibliographical references and indexes
Keywords: Bible -- Language, style; Greek language, Biblical -- Grammar; Lehrbuch